The Today's Relevance of Anti-Laws in Luxury Marketing - Ismailova, Madina; Král, Petr, 1979-; Stránská, Michaela; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis deals with the anti-laws of luxury marketing, which are the set of managerial principles summarized by Kapferer and Bastien used in strategic marketing. The anti-laws were developed during the 90s and early 00s. The goal of this thesis is to evaluate whether these anti-laws are relevant in the current environment. For this purpose, the thesis identifies luxury marketing anti-laws and analyses the core nature of their functionality by grouping them into categories with common drivers. Further, the thesis aims at identifying conditions under which these anti-laws remain truthful, and whether changes in technology, consumer behavior, or market trends have an impact on their relevancy. The main research input was provided through interviews with luxury marketing experts.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses